Socio-economic Factors Influencing the Education of Muslim Girls and Other Educationally Disadvantaged Groups of Slums in Delhi - Khan, Fauzia (JOURNAL OF INDIAN EDUCATION, 2022)
Okhla is an area in South-East Delhi, majorly dominated with Muslim population. The establishment of Jamia Millia Islamia, a central university in this area played a major role to attract people to this area and settle down. The slums in this area present a bad picture as they lack basic civic amenities. The present paper tries to comprehend the factors influencing the education of Muslims girls and girls of other educationally disadvantaged groups (OEDG) in the slums of Okhla. In order to understand the problems of these educationally disadvantaged groups, a detailed analysis of related policy, provisions, strategies and programs implemented by the Government of India for improvement of educational status of Muslim girls and girls of OEDG, has been done. Along with this, the socio-economic factors responsible for the educational backwardness of the sample have been explored in this study. Analysis of the study was done both qualitatively as well as quantitatively. The paper concludes that, at present, economic inequality is the major hindrance for achieving the goal of education in case of Muslim girls and OEDG girls of slums. The social factors such as cultural, environmental and familial matters are secondary reasons of dropout of slum girls in Okhla (DH News Service, 2011).